An application of FAHP-TOPSIS integrated method for selecting a university by first-year students in Zimbabwe - Emmanuel, Mutambara; Muzurura, Joe (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to apply a novel hybrid multi-criteria decision method that combines the fuzzy analytical hierarchical process and the technique for order preference by similarity to ideal solution (FAHP-TOPSIS) to rank Zimbabwe’s state universities. This is because the selection of a university by first-year students is a complex decision-making process that requires interrogation of often conflicting goals such as academic reputation, cost of tuition, epistemic value, and employability after graduating. The diversity of universities and students becomes an impediment to the proper decision-making process, especially when the ability and knowledge of prospective students to analyze various disciplines on offer and the quality of tuition is minimal. Quantitative data on predetermined multi-criteria were collected from ten academic experts who were selected using the purposive sampling technique. Our findings demonstrate that the University of Zimbabwe, Midlands State University, and the National University of Science and Technology are the most preferred institutions of higher learning on the basis of cost of tuition, academic reputation, epistemic value, and degree variety. Universities must ensure a wider menu of competitive degrees to attract more students and improve brand equity and, in turn, their ranking. The contribution of the study is creating a more robust and balanced methodology for ranking universities in Zimbabwe by incorporating carefully selected criteria that are often overlooked in conventional rankings.